Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 175959 by BaliramKumar last updated on 10/Sep/22

f(x) = x^6  − 100x^5  + 100x^4  − 100x^3  + 100x^2  − 100x + 100  f(99) = ?

f(x)=x6100x5+100x4100x3+100x2100x+100f(99)=?

Commented by infinityaction last updated on 10/Sep/22

 p =   x^6 +100{(1−x)+x^2 (1−x)+x^4 (1−x)}     p  =   x^6 +100(1−x){1+x^2 +x^4 }      G.P. sum of 1+x^2 +x^4  = ((x^6 −1)/(x^2 −1))     p  = x^6 −100(x−1)×((x^6 −1)/((1+x)(x−1)))     p =  x^6 −x^6 +1 = 1

p=x6+100{(1x)+x2(1x)+x4(1x)}p=x6+100(1x){1+x2+x4}G.P.sumof1+x2+x4=x61x21p=x6100(x1)×x61(1+x)(x1)p=x6x6+1=1

Commented by BaliramKumar last updated on 10/Sep/22

thanks   sir

thankssir

Answered by Rasheed.Sindhi last updated on 10/Sep/22

f(x) = x^6  − 100x^5  + 100x^4  − 100x^3  + 100x^2  − 100x + 100             =x^5 (x−100)+ 100x^4  − 100x^3  + 100x^2  − 100x + 100  f(99)=x^5 (99−100)+ 100x^4  − 100x^3  + 100x^2  − 100x + 100              =−x^5 + 100x^4  − 100x^3  + 100x^2  − 100x + 100              =x^4 (−x+100)− 100x^3  + 100x^2  − 100x + 100               =x^4 (−99+100)− 100x^3  + 100x^2  − 100x + 100               =x^4 − 100x^3  + 100x^2  − 100x + 100               =x^3 (x−100) + 100x^2  − 100x + 100                =x^3 (99−100) + 100x^2  − 100x + 100                =−x^3  + 100x^2  − 100x + 100              =x^2 (−x+100)− 100x + 100              =x^2 (−99+100)− 100x + 100              =x^2 − 100x + 100              =x(x− 100) + 100              =x(99− 100) + 100              =−x + 100              =−99 + 100               =1

f(x)=x6100x5+100x4100x3+100x2100x+100=x5(x100)+100x4100x3+100x2100x+100f(99)=x5(99100)+100x4100x3+100x2100x+100=x5+100x4100x3+100x2100x+100=x4(x+100)100x3+100x2100x+100=x4(99+100)100x3+100x2100x+100=x4100x3+100x2100x+100=x3(x100)+100x2100x+100=x3(99100)+100x2100x+100=x3+100x2100x+100=x2(x+100)100x+100=x2(99+100)100x+100=x2100x+100=x(x100)+100=x(99100)+100=x+100=99+100=1

Commented by BaliramKumar last updated on 10/Sep/22

thanks  sir

thankssir

Answered by Rasheed.Sindhi last updated on 10/Sep/22

f(99)=Remainder of   f(x)/(x−99)  By Synthetic Division:    determinant (((99)),1,(-100),(100),(-100),(100),(-100),(100)),(,,( +99),(-99),( +99),(-99),(     99),(-99)),(,1,(     -1),(     1),(    -1),(     1),(     -1),(  determinant ((1))^ )))  f(99)=1

f(99)=Remainderoff(x)/(x99)BySyntheticDivision:99)1100100100100100100+9999+999999991111111f(99)=1

Commented by Tawa11 last updated on 15/Sep/22

Great sirs.

Greatsirs.

Answered by Devendra291999 last updated on 10/Sep/22

Solution  Given  f(x)=x^6 −100x^5 +100x^4 −100x^3 +100x^2 −100x+100  f(99)=?  then  x=99⇒x+1=100 putt  f(x)=x^6 −(x+1)x^5 +(x+1)x^4 −(x+1)x^3 +(x+1)x^2 −(x+1)x+x+1  f(x)=x^6 −x^6 −x^5 +x^5 +x^4 −x^3 −x^2 +x^3 +x^2 −x^2 −x+x+1  f(x)=1  f(99)=1Answer

SolutionGivenf(x)=x6100x5+100x4100x3+100x2100x+100f(99)=?thenx=99x+1=100puttf(x)=x6(x+1)x5+(x+1)x4(x+1)x3+(x+1)x2(x+1)x+x+1f(x)=x6x6x5+x5+x4x3x2+x3+x2x2x+x+1f(x)=1f(99)=1Answer

Terms of Service

Privacy Policy

Contact: info@tinkutara.com